AN APPLICATIONS IN DETERMINING THE BEST REFRIGERATOR BY USING THE TOPSIS METHOD - Prayogo Selamat Sholihin; Arpan; Eko Haryanto (Sean Institute, 2022)
Electronics is one of the household needs where these tools are very helpful in maintaining the freshness of food or drinks, namely the refrigerator or refrigerator. At this time, many other products have electronic product brands with all their advantages. The current research chooses the best quality used refrigerators because many refrigerators can still be used. To overcome this, a decision support system is needed in determining the best refrigerator using the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) method.Because this method uses the principle that the chosen alternative (used refrigerator) must have the closest distance from the positive ideal solution and the farthest from the negative ideal solution from a geometric point of view by using Euclidean distance to determine the relative proximity of an alternative (used refrigerator) to the optimal solution so that have good calculations and make good decisions. The criteria used in the assessment are the brand of the refrigerator, the engine, the body of the refrigerator, the freezer (coolant) space, the thermostat, and the refrigerator door.